Adequacy of iodized salt and its associated factors among households in the Bahir Dar Zuria district, Northwest Ethiopia, 2022 - Temech, Emebet Chalachew; Said, Oumer; Endalik, Genete; Demilew, Yeshalem Mulugeta; Belay, Mahider Awoke; Kassie, Tadele Derbew; Dessie, Anteneh Mengist (Frontiers in Nutrition, 2023)
Background: The inadequacy of iodine in salt is the contributing factor behind ignorance and poor economic performance in developing countries. To address the issue of iodine deficiency, universal salt iodization has been implemented globally. Nevertheless, it is imperative to closely monitor the sufficiency of iodine in salts to achieve its intended objective at the household level in the Bahir Dar Zuria District. Objective: To assess the adequacy of iodized salt and its associated factors among households in Bahir Dar Zuria District, Northwest Ethiopia. Methods: A community-based cross-sectional study was conducted from May to June 2022 among households in Bahir Dar Zuria district. The data were gathered from 825 households that were chosen through a multistage sampling process. Iodometric titration was used to assess the amount of iodine in salt. The data were gathered using a structured questionnaire that was administered by an interviewer. For data entry and analysis, EpiData version 3.01 and SPSS version 25.0 were used, respectively. To evaluate the association between explanatory factors and the outcome variable, binary logistic regression was conducted, and significance was determined at alpha 0.05. Result: This study analyzed a total of 825 households. Of these, only 384 [46.5%, 95% CI: 43.5%-50.5%] households had adequately iodized salt at home. Age increase in one year [AOR=1.04, 95% CI=1.02-1.06], being an urban resident [AOR=3.18, 95% CI=1.84–5.48], diploma and above educational attainment [AOR=3.74, 95% CI=1.99-7.02], checking salt by asking the seller [AOR=2.21, 95% CI=1.26-3.88], storing salts in closed containers [AOR=1.57, 95% CI=1.13-2.19], and storing salts in a dry and cool area [AOR= 2.72, 95% CI =1.37-5.42] were associated with the adequacy of iodized salt at the household level. Conclusion and recommendation: The percentage of households in the district (46.5%) that had enough iodized salt in their homes is still extremely low and falls short of the targeted level for the country. At the household level, adequate iodized salt was associated with age, place of residence, level of education, checking salt iodization while purchasing, place of salt storage, and cover use for salt containers. Therefore, increasing the accessibility of iodized salt at the household level is essential.